Twin pregnancy outcome following teriflunomide treatment in a relapsing-remitting multiple sclerosis patient: A case report - D’Aleo, Giangaetano (Medicine (Baltimore), 2020)
RATIONALE: Teriflunomide is a disease-modifying drug that has been approved for treatment of relapsing-remitting multiple sclerosis. Due to its teratogenic effect in animals, however, it is not recommended during pregnancy. For this reason, effective contraception must be used during its administration. When an unscheduled pregnancy occurs during therapy, patients must undergo a cholestyramine procedure for rapid flushing of the drug. PATIENT CONCERNS: We describe the case of a 35-year-old female patient suffering diagnosed with relapsing-remitting multiple sclerosis at the age of 20. The patient as a result of side effects of previous therapies started taking teriflunomide. DIAGNOSIS: Despite recommendations for the use of contraceptives, the patient became pregnant during drug therapy. Pregnancy occurred 12 months after initiating teriflunomide treatment. INTERVENTIONS: Therapy with teriflunomide was immediately suspended and cholestyramine was prescribed (8 g 3 times a day, for 11 days) to flush out any residual drug from the body. OUTCOMES: Despite an 8-week exposure to teriflumomide during gestation, the patient gave birth to healthy twin girls at 35(th) week. Controls carried out after birth did not reveal any malformation or genetic and chromosomal abnormality. At a 5-month pediatric specialist check both babies were healthy and growing regularly. CONCLUSION: This shows that even if there is evidence of teratogenic effects in animals, an 8-week exposure to teraflunomide >0.02 mg/L did not have effects on the newborn.